Mapping the recent advancements in bast fiber reinforced biocomposites: A review on fiber modifications, mechanical properties, and their applications - Md. Syduzzaman; Shaida Sultana Rumi; Fahmida Faiza Fahmi; Mahmuda Akter; Rasheda Begum Dina (Results in Materials, 2023)
Fiber reinforced polymer composites (FRPCs), due to their multifunctional properties, have already occupied a significant place in various applications such as aerospace, automotive, marine, structural engineering, and healthcare industries. Lightweight FRPCs are preferred over heavier materials because of some key advantages, such as high strength-to-weight ratio, corrosion resistance, design flexibility, fatigue resistance, damping properties, and electrical and thermal insulation properties. Though synthetic fibers such as carbon, glass, aramid fiber reinforced composites are found to provide better performance, these fibers are expensive as well as impose adverse impacts on the environment. Currently, bast fiber reinforced biocomposites (BFBCs) are receiving increasing attention due to their biodegradability, availability, low cost, and higher strength-to-weight ratio. Researchers are working rigorously on BFBCs to unveil their optimal properties. BFBCs can be disposed of easily without affecting the environment. BFBCs, with their sustainable and biodegradable properties, notably promote the use of natural fibers particularly bast fibers and minimize the consumption of expensive and non-degradable synthetic fibers reinforcements in the composite industry. This paper provides an overview of the use of different natural fibers in reinforcing polymer composites for various applications to achieve sustainability. The influence of various fibrous preforms of bast fibers on the mechanical behavior of BFBCs, and their prospects are comprehensively reviewed.